2022
DOI: 10.3389/fgene.2022.907774
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DUXAP8 as a prognostic biomarker for various cancers: A meta-analysis and bioinformatics analysis

Abstract: Background: Dual homeoboxes A pseudogene 8 (DUXAP8) is a newly discovered long noncoding RNA that has been shown to function as an oncogene in a variety of human malignant cancers. By integrating available data, this meta-analysis sought to determine the relationship between clinical prognosis and DUXAP8 expression levels in diverse malignancies.Materials and methods: A systematic search was performed to identify eligible studies from several electronic databases from their inception to 25 October 2021. Pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ). LncRNA DUXAP8 acts as an oncogene in most tumors, its abnormal overexpression is associated with the proliferation, invasion, migration, anti-autophagy, and poor prognosis of tumors ( Wang et al, 2022a ; Wang et al, 2022b ), it may act as a potential therapeutic target for cancer ( Wang et al, 2022b ); in a research on identification of necroptosis-related lncRNAs in hepatocellular carcinoma, DUXAP8 was identified as a prognostic lncRNA and related to patients’ prognosis ( Chen et al, 2022b ); In addition to our research, other studies have also found that it is involved in the process of ferroptosis in tumor, such as: it can act with ferroptosis-associated gene FANCD2 to form DUXAP8-miR-29c-FANCD2 axe in hepatocellular carcinoma ( Yang et al, 2022 ), it was also identified as one of ferroptosis-related lncRNAs in kidney carcinoma ( Xing et al, 2021 ). Similar to DUXAP8, lncRNA PVT1 was considered as involved in the ferroptosis progress, it may regulate ferroptosis through miR-214-mediated TFR1 and TP53 expression ( Lu, Xu & Lu, 2020 ), it was identified as one of the ferroptosis-related lncRNAs to construct a panel for predicting tumor progression, microenvironment ( He et al, 2021 ), and radiotherapy response ( Zheng et al, 2021 ) in glioma; in liver cancer, PVT1 is involved in the regulatory mechanism of lncPVT1/miR-214-3p/GPX4 axis and plays a role in ketamine suppressing the viability of liver cancer cells and inducing ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01426 modulates CTBP1/miR-423-5p/FOXM1 axis via interacting with IGF2BP1 to aggravate ccRCC progression ( Jiang et al, 2021b ), it also aggravates the malignant progression through miR-661/Mdm2 axis in glioma ( Shu et al, 2022 ), it serves as a prognostic indicator in lung adenocarcinoma by triggering growth and metastasis ( Deng et al, 2022 ), what’s more, in a recently reported study on ferroptosis-related lncRNAs of glioma, LINC01426 was identified to be related to ferroptosis, its knockdown could significantly increase in the Fe 2+ levels and the erastin-induced ROS levels in glioma cells ( Huang et al, 2022 ). LncRNA DUXAP8 acts as an oncogene in most tumors, its abnormal overexpression is associated with the proliferation, invasion, migration, anti-autophagy, and poor prognosis of tumors ( Wang et al, 2022a ; Wang et al, 2022b ), it may act as a potential therapeutic target for cancer ( Wang et al, 2022b ); in a research on identification of necroptosis-related lncRNAs in hepatocellular carcinoma, DUXAP8 was identified as a prognostic lncRNA and related to patients’ prognosis ( Chen et al, 2022b ); In addition to our research, other studies have also found that it is involved in the process of ferroptosis in tumor, such as: it can act with ferroptosis-associated gene FANCD2 to form DUXAP8-miR-29c-FANCD2 axe in hepatocellular carcinoma ( Yang et al, 2022 ), it was also identified as one of ferroptosis-related lncRNAs in kidney carcinoma ( Xing et al, 2021 ). Similar to DUXAP8, lncRNA PVT1 was considered as involved in the ferroptosis progress, it may regulate ferroptosis through miR-214-mediated TFR1 and TP53 expression ( Lu, Xu & Lu, 2020 ), it was identified as one of the ferroptosis-related lncRNAs to construct a panel for predicting tumor progression, microenvironment ( He et al, 2021 ), and radiotherapy response ( Zheng et al, 2021 ) in glioma; in liver cancer, PVT1 is involved in the regulatory mechanism of lncPVT1/miR-214-3p/GPX4 axis and plays a role in ketamine suppressing the viability of liver cancer cells and inducing ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 5-year survival rate remains relatively low for most cancers. Human health is seriously threatened by cancer [ 56 ]. piRNAs are a class of small non-coding RNA molecules that are expressed in the germline of many species [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a research reported that overexpressed miR-365 under hypoxic conditions could target the 3’UTR of the HLA-G mRNA to suppress its expression [ 49 ]. Accumulating evidence has shown that long non-coding RNAs (lncRNAs) could be novel biomarkers to predict the prognosis of patients with cancer [ 50 ]. According to Wang et al’s report [ 51 ], lncRNA myocardial infarction associated transcript (MIAT) was correlated with poor OS, and it was noted that MIAT and miR-133 participated in the proliferation and metastasis of pancreatic cancer [ 52 ].…”
Section: Discussionmentioning
confidence: 99%